Muscle-Strengthening Activities and Cancer Incidence and Mortality: A Systematic Review and Meta-Analysis of Observational Studies - De Moraes-Ferrari, G (BioMed Central Ltd, 2021)
Background: Physical activity has been associated with reduced risk of seven types of cancer. It remains unclear, however, whether muscle-strengthening activities also reduce cancer incidence and mortality. Methods: PubMed, Embase, Web of Science and Scopus were searched from inception to March 2020. Summary hazard ratio (HR) and 95% confidence intervals (CI) were estimated using random-effects models. Results: Twelve studies (11 cohorts; 1 case-control), 6 to 25 years of follow-up, including 1,297,620 participants, 32,196 cases and 31,939 deaths, met inclusion criteria. Muscle-strengthening activities were associated with a 26% lower incidence of kidney cancer (HR for high vs low levels of muscle-strengthening activities: 0.74; 95% CI 0.56 to 0.98; I2 0%; 2 studies), but not with incidence of other 12 types of cancer. Muscle-strengthening activities were associated with lower total cancer mortality: HRs for high vs low levels of muscle-strengthening activities was 0.87 (95% CI 0.73 to 1.02; I2 58%; 6 studies); and HR for ≥2 times/week vs < 2 times/week of muscle-strengthening activities was 0.81 (95% CI 0.74 to 0.87; I2 0%; 4 studies). Regarding the weekly duration of muscle-strengthening activities, HR for total cancer mortality were 0.91 (95% CI 0.82 to 1.01; I2 0%; 2 studies) for 1–59 min/week and 0.98 (95% CI 0.89 to 1.07; I2 0%) for ≥60 min/week vs none. Combined muscle-strengthening and aerobic activities (vs none) were associated with a 28% lower total cancer mortality (HR 0.72; 95% CI 0.53 to 0.98; I2 85%; 3 studies). Conclusions: Muscle-strengthening activities were associated with reduced incidence of kidney cancer and total cancer mortality. Combined muscle-strengthening and aerobic activities may provide a greater reduction in total cancer mortality. © 2021, The Author(s).